The transcription elongation factors Spt4 and Spt5 control neural progenitor proliferation and are implicated in neuronal remodeling during Drosophila mushroom body development - Barthel, Lea; Pettemeridi, Stefani; Nebras, Ali; Schnaidt, Hayley; Fahland, Karoline; Vormwald, Lea; Raabe, Thomas (Frontiers in Cell and Developmental Biology, 2024)
Spt4 and Spt5 form the DRB sensitivity inducing factor (DSIF) complex that regulates transcription elongation at multiple steps including promotor-proximal pausing, processivity and termination. Although this implicated a general role in transcription, several studies pointed to smaller sets of target genes and indicated a more specific requirement in certain cellular contexts. To unravel common or distinct functions of Spt4 and Spt5 in vivo, we generated knock-out alleles for both genes in Drosophila melanogaster. Using the development of the mushroom bodies as a model, we provided evidence for two common functions of Spt4 and Spt5 during mushroom body development, namely control of cell proliferation of neural progenitor cells and remodeling of axonal projections of certain mushroom body neurons. This latter function is not due to a general requirement of Spt4 and Spt5 for axon pathfinding of mushroom body neurons, but due to distinct effects on the expression of genes controlling remodeling.